Self-compacting emulsified asphalt mixture paving and its construction method
Patent Information
- Application Number
- CN202611221368.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
然而,常规的乳化沥青混合料初期强度形成缓慢,养生周期通常需要3至7天甚至更长时间才能开放交通,无法满足城市道路快速维修和高速公路应急抢修工程的需求
[0021]1)本发明创新性地采用三层连续式浇筑摊铺的自密实乳化沥青混合料,通过材料配伍优化赋予了混合料优异的自密实性能,摊铺后无须碾压即可达到设计密实度,完全摒弃了传统路面施工中的压路机碾压工序,不仅大幅简化了施工流程、缩短了施工周期,也消除了因碾压不当(欠压或过压)而导致的路面病害隐患。
Smart Images

Figure CN123005784A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road engineering materials and construction technology, specifically relating to a self-compacting emulsified asphalt mixture cast-in-place pavement and its construction method. Background Technology
[0002] Asphalt pavement, with its advantages of comfortable driving, low noise, and relatively short construction period, has become the mainstream pavement form for high-grade highways and urban roads. Traditional hot-mix asphalt pavement construction requires heating aggregates and asphalt to temperatures above 150°C, resulting in high energy consumption, large carbon emissions, and stringent requirements for ambient temperature, significantly limiting its application in cold seasons or remote areas. Furthermore, the paving and shaping of traditional hot-mix asphalt pavement relies on multiple passes of compaction with a road roller. Insufficient compaction can easily lead to early water damage and loosening and spalling, while over-compaction can cause aggregate breakage, thereby destroying the interlocking structure, both of which adversely affect the long-term performance of the pavement.
[0003] Emulsified asphalt mixtures, as a room-temperature mixing material, can significantly reduce energy consumption and exhaust emissions, exhibiting outstanding environmental benefits and gaining increasing attention in the road engineering field. However, conventional emulsified asphalt mixtures develop initial strength slowly, and the curing period typically requires 3 to 7 days or even longer before traffic can resume, failing to meet the needs of rapid maintenance of urban roads and emergency repairs on highways. While some semi-flexible pavement materials have been reported in existing research, most focus on grouting-type semi-flexible pavements—that is, injecting cement-based or resin-based grouting materials into an open-graded, large-pore asphalt mixture matrix. This process is cumbersome (matrix paving and compaction → grouting → curing), and the significant stiffness difference between the large-pore matrix and the grouting material results in insufficient interfacial adhesion, easily leading to shrinkage cracking and other problems. Furthermore, existing semi-flexible pavement technologies mostly employ hot-mix processes to prepare the matrix asphalt mixture, failing to fully leverage the environmentally friendly construction advantages of emulsified asphalt. For example, the Hebei Provincial Local Standard DB13 / T 6175-2025, "Technical Specification for Construction of Semi-Flexible Composite Pavement," specifies grouted semi-flexible pavement, which, while possessing good rutting resistance, has a complex construction process requiring two stages, resulting in low overall efficiency. Tianjin Municipal Standard TJG / TF3001-2025, "Technical Specification for Grouted Semi-Flexible Rutting-Resistant Asphalt Pavement," and the group standard T / JSJTQX 70-2025, "Technical Specification for Construction of Ultra-High Performance Mixed Semi-Flexible Asphalt Pavement," also primarily focus on grouted or mixed semi-flexible asphalt pavement, but there is still significant room for improvement in simplifying the process and rapidly opening it to traffic.
[0004] Therefore, how to develop a new type of pavement structure and its construction method that combines the advantages of environmentally friendly construction of emulsified asphalt, enables rapid traffic opening, does not require compaction, and has excellent structural load-bearing performance has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] This invention aims to solve the aforementioned problems in the prior art and provides a self-compacting emulsified asphalt mixture cast-in-place pavement and its construction method. This pavement structure involves the continuous layering and paving of three layers of self-compacting emulsified asphalt mixture with different gradations. Through synergistic optimization of material compatibility and structural combination, it achieves the construction goal of "self-compacting upon paving, no compaction required, and traffic open within 4 to 6 hours." It is particularly suitable for pavement projects prone to rutting, such as heavy traffic sections, long longitudinal slopes, bus lanes, service areas, and road intersections, as well as rapid repair projects. The specific technical solution is as follows:
[0006] A self-compacting emulsified asphalt mixture cast-in-place pavement, the pavement comprising a subbase and a self-compacting emulsified asphalt surface layer laid on the subbase, wherein a tack coat is provided between the subbase and the self-compacting emulsified asphalt surface layer.
[0007] The self-compacting emulsified asphalt surface layer comprises, from bottom to top, a bottom layer, a middle layer, and a top layer. The total thickness of the self-compacting emulsified asphalt surface layer is 15–20 cm; the thickness of the bottom layer is 7–9 cm, the thickness of the middle layer is 5–7 cm, and the thickness of the top layer is 3–4 cm; all three layers are made of self-compacting emulsified asphalt mixture.
[0008] Furthermore, the self-compacting emulsified asphalt mixture comprises the following components by weight: 70-80 parts aggregate, 6-11 parts inorganic early-strength agent, 4-7 parts filler, and 10-12 parts modified emulsified asphalt; the modified emulsified asphalt comprises the following components by weight: 62-65% modified asphalt, 24-29% water, 5-8% cationic emulsifier, 1.5-2.5% stabilizer, and 1.5-2.5% pH adjuster; the modified asphalt is obtained by composite modification of SBS, SBR, and rubber powder.
[0009] Furthermore, the bottom layer uses an AC-25 gradation, the middle layer uses an AC-20 gradation, and the top layer uses an AC-13 gradation.
[0010] Furthermore, in the modified asphalt, the mass ratio of SBS, SBR, and rubber powder is 3-5:3-7:1-3. The modified asphalt in this invention requires the use of a special modified emulsified asphalt to give it excellent hydrophilicity and stability. After modification with the modifiers in the above proportions, the residual index of the modified emulsified asphalt in this invention can reach PG82-34, and its storage stability is greater than 2 years. Furthermore, the cationic emulsifier is a compound of a modified cationic emulsifier containing polyoxyethylene / polysiloxane blocks and a di-long-chain alkyl dimethyl benzyl ammonium chloride derivative at a mass ratio of 1.5-2.5:1. The cationic emulsifier used in this invention possesses superior emulsifying performance and excellent slow-cracking function, enabling it to emulsify the above-mentioned modified components, mix them with asphalt, and allow the emulsified modified asphalt, aggregates, and early-strength agents to be mixed, paved, and poured without the need for additional water.
[0011] Furthermore, the early-strength agent comprises the following mass fractions: 65-75 parts of fast-acting cement, 3-7 parts of nanocellulose, 12-18 parts of calcium formate, and 8-12 parts of sodium sulfate. In this invention, the early-strength agent, as an inorganic composite material, uses water from the emulsified asphalt material as the reaction water, allowing the three processes of early-strength agent hydration, asphalt demulsification, and polymer film formation to occur simultaneously and alternately. The rigid skeleton and flexible network in the mixture are simultaneously formed, creating a three-dimensional interpenetrating network structure, which synergistically improves the early strength of the mixture. Controlling the ratio of calcium formate and sodium sulfate ensures the synergistic effect of early-strength agent hydration, asphalt demulsification, and polymer film formation rates.
[0012] Furthermore, the mass ratio of water content in the modified emulsified asphalt to the combined content of calcium formate and sodium sulfate in the accelerator is 8–21:1. In this invention, the water in the modified emulsified asphalt is directly used as the reaction water for the accelerator, eliminating the need for additional reaction water. This allows for precise control of the reaction between water and the accelerator, preventing water loss and evaporation, which could lead to weak interfaces and porosity. The resulting mixture possesses a dense and uniform physical composite structure, thus improving its performance.
[0013] Furthermore, the stabilizer is nano-silica or organobentonite.
[0014] Furthermore, the tack coat is SBS-modified emulsified asphalt, applied at a rate of 0.5–1 kg / m². Using SBS-modified emulsified asphalt as the tack coat in this invention allows for application at room temperature, avoiding thermal damage to the underlying layer caused by hot asphalt application. Furthermore, SBS modification imparts a higher softening point (≥80℃) and elastic recovery performance (≥95%) to the tack coat, maintaining good interlayer adhesion and stress absorption capacity under load. After demulsification due to water evaporation, the tack coat forms a thin but tough modified asphalt film, effectively enhancing the bond between the underlying layer and the self-compacting emulsified asphalt surface layer, preventing interlayer slippage. The demulsification rate of the SBS-modified emulsified asphalt is preferably slow-cracking, fast-cracking, or medium-cracking type to ensure rapid demulsification of the tack coat before paving the mixture, guaranteeing strength.
[0015] This invention also provides a construction method for cast-in-place self-compacting emulsified asphalt mixture pavement, comprising the following steps:
[0016] Step S1, Construction Preparation: Treat the subgrade and spray tack coat on the top surface of the subgrade; simultaneously, screen and dry-mix the aggregates of each grade evenly. Step S2, Paving: Determine the amount of modified emulsified asphalt and inorganic early-strength agent according to the aggregate gradation. Mix the self-compacting emulsified asphalt mixture on-site and pave it immediately. No compaction is required after paving. Step S3, Core Sampling and Opening: After paving is completed, take out complete core samples for observation and then open the road to traffic.
[0017] Furthermore, in step S2, the paving speed is 1.5-3 m / min; the paving is carried out by a combination of slurry seal truck and hot-mix asphalt paver.
[0018] Furthermore, the preparation method of the modified emulsified asphalt includes: heating the base asphalt to 140-145°C, adding 5% aromatic hydrocarbon oil and continuing to stir and heat to 175-180°C for 10-15 minutes; adding a stabilizer, then adding SBS, SBR and rubber powder, and swelling for 30-45 minutes; subsequently shearing at 3000-5000 rpm for 120-150 minutes, and then stirring and developing for 90-120 minutes to obtain modified asphalt; heating the modified asphalt to 170-180°C, and pumping it together with an emulsifier aqueous solution into a colloid mill for emulsification for 1 minute to obtain the modified emulsified asphalt; wherein, the amount of SBS is 3-5% of the amount of base asphalt, the amount of SBR is 3-7% of the amount of base asphalt, and the amount of rubber powder is 1-3% of the amount of base asphalt. Therefore, the demulsification rate of SBS, SBR, and rubber powder modified emulsified asphalt should be prioritized for slow-demulsification type to ensure that the mixture has sufficient breakage time and construction window during paving.
[0019] Furthermore, the emulsifier is a cationic emulsifier, which is a mixture of a modified cationic emulsifier containing polyoxyethylene / polysiloxane blocks and a di-long-chain alkyl dimethyl benzyl ammonium chloride derivative in a mass ratio of 1.5 to 2.5:1; the stabilizer is nano-silica or organobentonite.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) This invention innovatively adopts a three-layer continuous pouring and paving method for self-compacting emulsified asphalt mixture. Through material compatibility optimization, the mixture is endowed with excellent self-compacting properties. After paving, it can achieve the designed density without compaction. It completely eliminates the roller compaction process in traditional road construction, which not only greatly simplifies the construction process and shortens the construction cycle, but also eliminates the hidden dangers of road surface defects caused by improper compaction (under-compaction or over-compaction).
[0022] 2) This invention, through the introduction of inorganic early-strength agents and the optimized formulation of modified emulsified asphalt, enables the rapid formation of early strength in the mixture. Complete core samples can be extracted and traffic opened 4 to 6 hours after paving. This performance overcomes the bottleneck of the conventional 3-7 day curing period for emulsified asphalt mixtures, and shortens traffic closure time by more than 90% compared to traditional cold-recycled mixtures. It has extremely high practical value for the maintenance and emergency repair of urban expressways and highways with high traffic volume where long-term closures are not feasible.
[0023] 3) This invention employs a three-layer self-compacting emulsified asphalt mixture with different aggregate gradations—a bottom layer (AC-25), a middle layer (AC-20), and a top layer (AC-13)—to form the pavement surface layer. The interlayer modulus achieves a smooth transition, resulting in a more coordinated mechanical response of the pavement structure. Finite element analysis shows that, compared to single hot-mix asphalt pavement structures, hot-mix-self-compacting mixed structures, and double-layer self-compacting structures, the three-layer self-compacting structure of this invention significantly reduces the maximum tensile stress in each structural layer (approximately 13.5% reduction on the surface of the top layer, approximately 26.9% reduction on the bottom surface of the middle layer, and approximately 33.3% reduction on the bottom surface of the bottom layer), and also exhibits the lowest surface deflection value (approximately 14.7% reduction). This fully demonstrates that the three-layer self-compacting surface layer structure with different gradations of this invention possesses optimal comprehensive performance in terms of crack resistance, fatigue resistance, and overall stiffness.
[0024] 4) The total thickness of the self-compacting emulsified asphalt pavement of this invention is 18 cm. For a strong base and thin surface structure, this reduces the thickness by approximately 20% to 40% compared to traditional hot-mix asphalt pavement, thus reducing the pavement's self-weight while maintaining structural load-bearing capacity. Its excellent resistance to rutting, fatigue, and interlayer bonding makes it particularly suitable for heavy-load traffic sections, long longitudinal slopes, bus lanes, service areas, road intersections, toll stations, and airport pavements—sections prone to rutting and high shear stress. Furthermore, its ability to quickly open to traffic also gives it broad application prospects in maintenance, repair, and emergency repair projects. Attached Figure Description
[0025] Figure 1 This is a schematic cross-sectional view of the road surface structure in the experimental group of the present invention.
[0026] Figure 2 This is a schematic cross-sectional view of the road surface structure in Comparative Group 1 of the experimental examples of this invention;
[0027] Figure 3 This is a schematic cross-sectional view of the road surface structure in comparative group 2 of the experimental examples of this invention;
[0028] Figure 4 This is a cross-sectional schematic diagram of the road surface structure in comparative group 3 of the experimental examples of this invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments.
[0030] A self-compacting emulsified asphalt mixture cast-in-place pavement, the specific structure of which is shown in the attached figure. Figure 1 As shown, from bottom to top, there are a subbase and a self-compacting emulsified asphalt surface layer. A tack coat is laid between the subbase and the self-compacting emulsified asphalt surface layer. The self-compacting emulsified asphalt surface layer includes a bottom layer, a middle layer and a top layer.
[0031] The thickness of the self-compacting emulsified asphalt surface layer is 18cm; the thickness of the bottom layer is 8cm; the thickness of the middle layer is 6cm; and the thickness of the top layer is 4cm.
[0032] The application rate of the tack coat oil is 0.5-1 kg / m³. 2 The tack coat is emulsified asphalt, specifically SBS modified emulsified asphalt.
[0033] A construction method for cast-in-place self-compacting emulsified asphalt mixture pavement includes the following steps:
[0034] Step S1, Construction Preparation: First, level the subgrade, spray tack coat on the top surface of the subgrade, and at the same time, screen and dry mix the aggregates of each grade evenly.
[0035] Step S2, Paving: Determine the amount of emulsified asphalt based on the aggregate gradation, then determine the amount of early strength agent. Mix the self-compacting emulsified asphalt mixture on-site and then pave it on-site. No compaction is required after paving.
[0036] Step S3, Core Sampling and Observation: Core samples are taken for observation 4-6 hours after paving is completed.
[0037] Example 1
[0038] This embodiment provides a construction method for cast-in-place self-compacting emulsified asphalt mixture pavement, including the following steps:
[0039] Step S1, Construction Preparation: First, treat the subgrade layer, spray tack coat on the top surface of the subgrade layer, and at the same time, screen and dry mix the aggregates of each grade evenly.
[0040] Specifically, this embodiment is used for road repair construction. First, the road section to be repaired is milled. After milling, the road surface is cleaned to ensure it is dry, clean, and smooth. The milled roadside serves as the subbase. The subbase is checked for any other defects. Once the inspection is complete, emulsified asphalt is sprayed onto the subbase as a tack coat to improve the adhesion between the subbase and the subsequently laid self-compacting emulsified asphalt surface layer. In this embodiment, the emulsified asphalt is specifically SBS modified emulsified asphalt, and its spraying rate is 0.8 kg / m². 2 The technical specifications of SBS modified emulsified asphalt are shown in Table 1 below:
[0041] Table 1 Technical Specifications of SBS Modified Emulsified Asphalt
[0042]
[0043] Once the sprayed SBS modified emulsified asphalt has broken down and the water has evaporated, the next step of construction preparation can proceed.
[0044] Simultaneously, the aggregates used subsequently need to be screened and graded. The aggregates include coarse and fine aggregates. Coarse aggregates should be hard, rough, and angular in appearance, and their technical requirements should meet the requirements of JTG F40. Fine aggregates should be clean, dry, unweathered, and free of impurities. The sand equivalent of the fine aggregates should not be less than 60%, and other technical indicators should meet the requirements of JTG F40. It should be noted that the 0–2.36 mm aggregate in the fine aggregates is partially replaced by an early-strength agent. This avoids an excessive amount of 0–2.36 mm fine aggregates and ensures standardized gradation. The moisture content of the aggregates should not exceed 2%. If the moisture content is too high, it should be dried until the moisture content is below 2% and cooled to room temperature before use. The gradation of coarse and fine aggregates should be carried out according to AC-13, AC-20, and AC-25 standards, respectively. In this invention, the filler is mineral powder, which includes mineral powder obtained by grinding hydrophobic rocks such as limestone or strong basic rocks from igneous rocks. The fiber stabilizer used in this invention is basalt fiber, wherein the technical specifications of the basalt fiber are: average diameter less than or equal to 16 μm, tensile strength greater than or equal to 1000 MPa, elongation at break 2-3%, and tensile strength retention rate greater than or equal to 85%.
[0045] Step S2, paving: Determine the amount of modified emulsified asphalt based on the aggregate gradation, then determine the amount of early strength agent. Mix the self-compacting emulsified asphalt mixture on-site and then pave it on-site. No compaction is required after paving.
[0046] Specifically, based on the gradation in step S1, the dosage of modified emulsified asphalt and early strength agent is determined respectively. Among them, the aggregate of AC-25 gradation is used in the lower layer, and the dosage of early strength agent is relatively small.
[0047] The mix proportions of the self-compacting emulsified asphalt mixture were determined. On-site mixing and paving were employed. First, modified emulsified asphalt was prepared. The base asphalt was heated to 140–145°C, and 5% aromatic hydrocarbon oil was added. The mixture was then stirred and heated further, reaching 175–180°C and stirring for 10–15 minutes. A stabilizer was added; in this invention, nano-silica or organobentonite was used as the stabilizer. SBS, SBR, and rubber powder were added. After swelling for 30–45 minutes, the mixture was sheared at 3000–5000 rpm for 120–150 minutes. Finally, it was developed under the action of a mixer for 90–120 minutes to obtain the modified asphalt. In this invention, the amount of SBS in the modified asphalt was 3–5% of the base asphalt, SBR was 3–7% of the base asphalt, and rubber powder was 1–3% of the base asphalt. Commercially available base asphalt, such as Sinopec AH-70, was selected. The emulsifier is dissolved in water at 60-70°C by stirring, and then hydrochloric acid is added to adjust the pH to 2.5-3.5 to prepare an emulsifier aqueous solution. The modified asphalt prepared above is then heated to 170-180°C and pumped together with the emulsifier aqueous solution into a colloid mill for emulsification for 1 minute to obtain modified emulsified asphalt. After passing the technical tests, it is ready for use. In this invention, the softening point of the emulsified modified asphalt evaporation residue is ≥ 82°C, the ductility at 5°C is ≥ 34 cm, the solid content is ≥ 63%, the mechanical stability during transportation is < 0.1%, and the storage stability is ≥ 2 years. In this embodiment, a mixture of a modified cationic emulsifier containing polyoxyethylene / polysiloxane blocks and a di-long-chain alkyl dimethyl benzyl ammonium chloride derivative at a mass ratio of 1.5-2.5:1 is used as the cationic emulsifier.
[0048] The modified emulsified asphalt is mixed with aggregates of different gradations in the following weight proportions: 70-80 parts aggregate, 6-11 parts inorganic early strength agent, 4-7 parts filler and 10-12 parts modified emulsified asphalt. The mixture is then transported to a hot-mix asphalt paver via a conveyor belt while being mixed, and the paving speed is 1.5-3 m / min.
[0049] The first layer to be mixed and paved is the lower layer, which uses AC-25 aggregate with 80 parts, modified emulsified asphalt with 10 parts, inorganic accelerator with 6 parts, and filler with 4 parts, and has a paving thickness of 8cm. The middle layer uses AC-20 aggregate with 78 parts, emulsified asphalt with 10 parts, inorganic accelerator with 6 parts, and filler with 6 parts, and has a paving thickness of 6cm. The top layer uses AC-13 aggregate with 70 parts, modified emulsified asphalt with 12 parts, inorganic accelerator with 11 parts, and filler with 7 parts, and has a paving thickness of 4cm.
[0050] It should be noted that no compaction is required during the paving of any of the surface layers in this application, and the self-compacting emulsified asphalt mixture used in this application has self-compacting and self-healing functions.
[0051] Step S3, Core sampling and opening: After paving is completed, core samples are taken for observation and traffic is opened.
[0052] Specifically, after 4-6 hours of paving, a complete core sample can be extracted using a core drilling machine with a 150mm drill bit, at which point traffic can be opened. Initially, small vehicles are allowed to pass, and heavy vehicles are allowed to pass after 6 hours.
[0053] Experimental Example: The Influence of Surface Layer Structure on Road Performance
[0054] Experimental Methods: An experimental group and a control group were set up, with different pavement structures for each. The influence of pavement structure on pavement performance was studied by testing the maximum tensile stress and surface deflection at different locations. The control group consisted of three subgroups, with pavement structures as shown in the attached figure. Figure 2-4 As shown in the table, in comparison group 1, the pavement structure consists of a conventional hot-mix asphalt mixture for the lower and middle layers, and a self-compacting emulsified asphalt mixture for the upper layer. In comparison group 2, the pavement structure consists of a conventional hot-mix asphalt mixture for the upper layer, and self-compacting emulsified asphalt mixture for the middle and lower layers. In comparison group 3, the pavement structure is a two-layer self-compacting emulsified asphalt mixture. The test results are shown in the table below, where σ1 represents the maximum tensile stress on the surface of the upper layer, σ2 represents the maximum tensile stress on the bottom surface of the upper layer, σ3 represents the maximum tensile stress on the bottom surface of the middle layer, and σ4 represents the maximum tensile stress on the bottom surface of the lower layer.
[0055]
[0056] Experimental results:
[0057] (1) Example 1 is superior to the control group in all tensile stress indices of each structural layer. Compared with control group 1, the maximum tensile stress (σ1) on the surface of the upper layer of Example 1 is reduced by 13.5%, the maximum tensile stress (σ3) on the bottom surface of the middle layer is reduced by 24.0%, and the maximum tensile stress (σ4) on the bottom surface of the lower layer is reduced by 33.3%; compared with control group 2, σ3 of Example 1 is reduced by 13.6%, and σ4 is reduced by 20.0%; compared with control group 3 (double-layer self-compacting structure), σ1 of Example 1 is reduced by 18.2%, σ3 by 26.9%, and σ4 by 25.0%. The significant reduction in each stress index indicates that the three-layer fully self-compacting structure with different gradations of the present invention has a more reasonable stress transmission and dissipation path. The smooth transition of interlayer modulus and the synergistic effect of material properties effectively suppress the concentration of stress in each structural layer, thereby improving the crack resistance and fatigue resistance of the pavement.
[0058] (2) The surface deflection values of Example 1 were 14.8%, 9.4% and 11.6% lower than those of Comparison Group 1, Comparison Group 2 and Comparison Group 3, respectively, indicating that the overall stiffness and bearing capacity of the three-layer self-compacting pavement structure were optimal and the surface deformation control capability was the strongest. This is of great engineering significance for controlling rutting and extending the service life of the pavement.
[0059] Although the total thickness of the comparative group 3 (double-layer self-compacting structure) is similar to that of Example 1, its σ1 and σ3 indices are significantly higher than those of Example 1 due to the lack of modulus transition and stress buffering effect of the middle layer. This indicates that the three-layer structure with different gradations is not only conducive to the smooth transition of modulus, but also more effectively disperses the tensile stress inside each layer and delays the development of fatigue failure.
[0060] The higher σ4 (bottom surface of the lower layer) in comparison group 1 (where the self-compacting material is only used as the top layer) indicates that placing the self-compacting material in the top layer has a limited stress-relieving effect on the deeper structural layers (bottom layer). The higher σ1 in comparison group 2 (where the self-compacting material occupies the middle and lower layers) shows that the self-compacting material is insufficient in controlling tensile stress when used as a shallow layer. In contrast, the uniformly distributed three-layer structure in Example 1 achieved a balanced and low stress level at each layer, proving that using self-compacting emulsified asphalt mixture throughout the full thickness of the three-layer structure is the optimal structural combination.
[0061] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered exemplary and not restrictive in all respects. Furthermore, it should be understood that although this specification describes embodiments, it does not encompass only one technical solution. This descriptive method is merely for clarity, and those skilled in the art should consider the specification as a whole. The technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A self-compacting emulsified asphalt mixture cast-in-place pavement, characterized in that: The road surface includes a subbase and a self-compacting emulsified asphalt surface layer laid on the subbase, with a tack coat between the subbase and the self-compacting emulsified asphalt surface layer. The self-compacting emulsified asphalt surface layer comprises, from bottom to top, a bottom layer, a middle layer, and a top layer. The total thickness of the self-compacting emulsified asphalt surface layer is 15-20 cm. The thickness of the bottom layer is 7-9 cm, the thickness of the middle layer is 5-7 cm, and the thickness of the top layer is 3-4 cm. The bottom layer, middle layer, and top layer are all made of self-compacting emulsified asphalt mixture.
2. The self-compacting emulsified asphalt mixture cast-in-place pavement according to claim 1, characterized in that: The total thickness of the self-compacting emulsified asphalt surface layer is 18 cm; the thickness of the bottom layer is 8 cm, the thickness of the middle layer is 6 cm, and the thickness of the top layer is 4 cm.
3. The self-compacting emulsified asphalt mixture cast-in-place pavement according to claim 1, characterized in that: The self-compacting emulsified asphalt mixture comprises the following components by weight: 70-80 parts aggregate, 6-11 parts inorganic early-strength agent, 4-7 parts filler, and 10-12 parts modified emulsified asphalt; the modified emulsified asphalt comprises the following components by mass fraction: 62-65% modified asphalt, 24-29% water, 5-8% cationic emulsifier, 1.5-2.5% stabilizer, and 1.5-2.5% pH adjuster; the modified asphalt is obtained by composite modification of SBS, SBR, and rubber powder; in the modified asphalt, the mass ratio of SBS, SBR, and rubber powder is 3-5:3-7:1-3.
4. The self-compacting emulsified asphalt mixture cast-in-place pavement according to claim 1, characterized in that: The tack coat is SBS modified emulsified asphalt, and the application rate is 0.5-1 kg / m²; the demulsification rate of the SBS modified emulsified asphalt is fast-breaking or medium-breaking type.
5. The self-compacting emulsified asphalt mixture cast-in-place pavement according to claim 1, characterized in that: The bottom layer uses AC-25 gradation, the middle layer uses AC-20 gradation, and the top layer uses AC-13 gradation.
6. The self-compacting emulsified asphalt mixture cast-in-place pavement according to claim 1, characterized in that: The mass ratio of water content in the modified emulsified asphalt to the combined content of calcium formate and sodium sulfate in the early-strength agent is 8–21:
1.
7. A construction method for cast-in-place pavement using self-compacting emulsified asphalt mixture as described in any one of claims 1 to 6, characterized in that: Includes the following steps: Step S1, Construction Preparation: Treat the subgrade and spray tack coat on the top surface of the subgrade; simultaneously, screen and dry-mix the aggregates of each grade evenly. Step S2, Paving: Determine the amount of modified emulsified asphalt and inorganic early-strength agent according to the aggregate gradation. Mix the self-compacting emulsified asphalt mixture on-site and pave it immediately. No compaction is required after paving. Step S3, Core Sampling and Opening: After paving is completed, take out complete core samples for observation and then open the road to traffic.
8. The construction method for cast-in-place self-compacting emulsified asphalt mixture pavement according to claim 7, characterized in that: In step S2, the paving speed is 1.5-3 m / min; the paving is carried out by a combination of slurry seal truck and hot-mix asphalt paver.
9. A construction method for cast-in-place self-compacting emulsified asphalt mixture pavement as described in claim 7, characterized in that: The method for preparing the modified emulsified asphalt includes: heating the base asphalt to 140-145°C, adding 5% aromatic hydrocarbon oil and continuing to stir and heat to 175-180°C for 10-15 minutes; adding a stabilizer, then adding SBS, SBR, and rubber powder, and swelling for 30-45 minutes; subsequently shearing at 3000-5000 rpm for 120-150 minutes, and then stirring and developing for 90-120 minutes to obtain the modified asphalt; heating the modified asphalt to 170-180°C, and pumping it together with an emulsifier aqueous solution into a colloid mill for emulsification for 1 minute to obtain the modified emulsified asphalt; wherein, the amount of SBS is 3-5% of the amount of base asphalt, the amount of SBR is 3-7% of the amount of base asphalt, and the amount of rubber powder is 1-3% of the amount of base asphalt.
10. A construction method for cast-in-place self-compacting emulsified asphalt mixture pavement as described in claim 7, characterized in that: The emulsifier is a cationic emulsifier, which is a mixture of a modified cationic emulsifier containing polyoxyethylene / polysiloxane blocks and a dimethyl benzyl ammonium chloride derivative in a mass ratio of 1.5 to 2.5:1; the stabilizer is nano-silica or organobentonite.
